Tele-forensic interviewing can be a reasonable alternative to face-to-face interviewing of child witnesses - Dickinson, Jason J; Lytle, Nicole E; Poole, Debra Ann (Law and human behavior, 2021)
Tele-forensic interviews have the potential to aid investigations when children live far from interviewers, there is a risk of disease transmission, or when expertise is not locally available. However, it is unknown whether tele-forensic interviewing is an effective alternative to face-to-face interviewing, particularly for children most prone to suggestibility and lapses of attention.OBJECTIVETele-forensic interviews have the potential to aid investigations when children live far from interviewers, there is a risk of disease transmission, or when expertise is not locally available. However, it is unknown whether tele-forensic interviewing is an effective alternative to face-to-face interviewing, particularly for children most prone to suggestibility and lapses of attention.Previous studies suggested that school-age children would provide similar amounts of information across interview modes but provided no basis for predicting how misinformation impacts accuracy across modes or how 4- and 5-year-olds would react to tele-forensic interviewing.HYPOTHESESPrevious studies suggested that school-age children would provide similar amounts of information across interview modes but provided no basis for predicting how misinformation impacts accuracy across modes or how 4- and 5-year-olds would react to tele-forensic interviewing.Children (4-8 years, N = 261, Mage = 6.42 years, 48% female) interacted with male assistants who violated a no-touching rule, parents read children a book containing misinformation about that event, and female assistants conducted interviews (usually 2 weeks after the event) face-to-face or via a video conference application.METHODChildren (4-8 years, N = 261, Mage = 6.42 years, 48% female) interacted with male assistants who violated a no-touching rule, parents read children a book containing misinformation about that event, and female assistants conducted interviews (usually 2 weeks after the event) face-to-face or via a video conference application.The children were more talkative during a practice narrative phase when interviewed face-to-face rather than on screen (incidence rate ratio [IRR] = 1.26, 95% CI [1.06, 1.51]), and 4-, 5-, and 6-year-olds said more in response to open-ended prompts when interviewed face-to-face (IRR = 1.50, 95% CI [1.08, 2.09]). Children younger than 7 years also disclosed the face touch and noncompleted handshake in response to earlier and less directive prompts when interviewed face-to-face, rs(53) = .28, p = .037, and rs(48) = .33, p = .021, respectively. Children 8 years and older, however, disclosed the face touch more readily when they spoke on screen, rs(28) = -.38, p = .036, and older 7-year-olds and 8-year-olds disclosed the noncompleted handshake more readily on screen, rs(30) = -.36, p = .042. Across interview modes, children reported comparable numbers of touch events, however, and were equally accurate on challenging source-monitoring and detail questions.RESULTSThe children were more talkative during a practice narrative phase when interviewed face-to-face rather than on screen (incidence rate ratio [IRR] = 1.26, 95% CI [1.06, 1.51]), and 4-, 5-, and 6-year-olds said more in response to open-ended prompts when interviewed face-to-face (IRR = 1.50, 95% CI [1.08, 2.09]). Children younger than 7 years also disclosed the face touch and noncompleted handshake in response to earlier and less directive prompts when interviewed face-to-face, rs(53) = .28, p = .037, and rs(48) = .33, p = .021, respectively. Children 8 years and older, however, disclosed the face touch more readily when they spoke on screen, rs(28) = -.38, p = .036, and older 7-year-olds and 8-year-olds disclosed the noncompleted handshake more readily on screen, rs(30) = -.36, p = .042. Across interview modes, children reported comparable numbers of touch events, however, and were equally accurate on challenging source-monitoring and detail questions.Tele-forensic interviewing can be a reasonable alternative to face-to-face interviewing. (PsycInfo Database Record (c) 2021 APA, all rights reserved).CONCLUSIONSTele-forensic interviewing can be a reasonable alternative to face-to-face interviewing. (PsycInfo Database Record (c) 2021 APA, all rights reserved).